On lengthening the voltage pulse duration of a linear modulator - Zakutin, V.V; Reshetnyak, N.K.; Romas’ko, V.P.; Chertishchev, I.A. (Вопросы атомной науки и техники, 2006)
Experiments were made to investigate the operation of the modulator in combination with the storage capacitor,
using the nonlinear properties of the core material of the pulse transformer for the formation of long pulses. Studies
were made on the parameters of voltage pulses at the secondary winding of the pulse step-up transformer. We have
considered the influence of the PT core demagnetization current and voltage on the shape of the output signal. Проведены эксперименты по исследованию работы модулятора с накопительной емкостью, с целью использования нелинейных свойств материала сердечника импульсного трансформатора для формирования импульсов большой длительности. Изучались параметры импульсов напряжения на вторичной обмотке импульсного трансформатора. Рассмотрено влияние тока размагничивания сердечника импульсного трансформатора и напряжения на форму выходного сигнала. Проведені експерименти по дослідженню роботи модулятора з накопичуваною ємністю, з метою
використовування нелінійних властивостей матеріалу осердя імпульсного трансформатора задля
формування імпульсів великої довжини. Вивчалися параметри імпульсів напруження на вторинній обмотці
імпульсного трансформатора. Розглянуто вплив струму розмагнічування та напруги на форму вихідного
імпульсу.